2018
DOI: 10.4317/medoral.22238
|View full text |Cite
|
Sign up to set email alerts
|

Association of time under immunosuppression and different immunosuppressive medication on periodontal parameters and selected bacteria of patients after solid organ transplantation

Abstract: BackgroundAim of this study was to investigate the association of the time under immunosuppression and different immunosuppressive medication on periodontal parameters and selected periodontal pathogenic bacteria of immunosuppressed patients after solid organ transplantation (SOT).Material and Methods169 Patients after SOT (lung, liver or kidney) were included and divided into subgroups according their time under (0-1, 1-3, 3-6, 6-10 and >10 years) and form of immunosuppression (Tacrolimus, Cyclosporine, Mycop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 29 publications
(44 reference statements)
0
15
0
1
Order By: Relevance
“…Bacteria and viruses are more often detected in oral biofilm samples of immunocompromised compared with systemically healthy individuals . However, studies have shown increased concentrations of viruses in the subgingival oral biofilm of systemically healthy patients with periodontal and peri‐implant diseases compared with their respective controls.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacteria and viruses are more often detected in oral biofilm samples of immunocompromised compared with systemically healthy individuals . However, studies have shown increased concentrations of viruses in the subgingival oral biofilm of systemically healthy patients with periodontal and peri‐implant diseases compared with their respective controls.…”
Section: Introductionmentioning
confidence: 99%
“…Bacteria and viruses are more often detected in oral biofilm samples of immunocompromised compared with systemically healthy individuals. 21,22 However, studies 18,20 have shown increased concentrations of viruses in the subgingival oral biofilm of systemically healthy patients with periodontal and peri-implant diseases compared with their respective controls. It is therefore evident that immunosuppression and bacterial colonization in the oral biofilm is not solely responsible for the development and progression of periodontal and peri-implant diseases; and presence of viruses in the subgingival oral biofilm of systemically healthy individuals may also play a role in this context.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, a recent study evaluated the relationships between immunosuppressive agents and periodontal pathogenic bacteria in patients following solid organ transplantation [124]. Although it should be noted that the study population included three different types of organs (kidney, liver, and lung), the study demonstrated that changes in the levels of periodontal pathogenic bacteria dependent on immunosuppressive agents.…”
Section: Periodontal Pathogens In Chronic Kidney Disease and Kidnementioning
confidence: 99%
“…3 The etiology of CsA-induced gingival overgrowth still remains incompletely explained 4 and many risk factors have been associated with its development and progression. 5 The accumulation of dental plaque 6 and inflammatory mediators associated with periodontal disease 7,8 have been suggested as local factors of gingival overgrowth. The studies are not conclusive about the requirement of accumulation of dental plaque for the initial lesion or if it is a consequence of gingival overgrowth.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, patients post solid organ transplantation, under medication with Cyclosporine, demonstrated worse periodontal condition compared to patients without Cyclosporine, since immunosuppression changed prevalence of selected potentially periodontal pathogenic bacteria. 6 The histopathological studies of CsA-induced gingival overgrowth have been demonstrated the enlargement of epithelial and connective tissue. However, most of them, investigated the influence of fibroblasts 10,11 and inflammatory cells on this process 12 ; the importance of epithelial hyperplasia on gingival overgrowth have been infrequently studied.…”
Section: Introductionmentioning
confidence: 99%